Penegakan Hukum dalam Penyelesaian Sengketa Transaksi Electronic Commerce - Ni Luh Kadek Dwi Fenny Febriyanti; I Nyoman Putu Budiartha; Ni Made Spasutari Ujianti (Jurnal Interpretasi Hukum, 2020)
E-commerce transaction as a trade transaction contract between sellers and buyers using the internet media provide convenience for both consumers and businesses, but these transactions also have some weaknesses that can lead to legal problems. This research discusses issues regarding the validity of the agreement related to e-commerce transactions and the law enforcement efforts in resolving e-commerce transaction disputes. This research uses a normative research method with a statute and conceptual approach. The collection of legal materials is carried out using the literature study method which is then systematically compiled and analyzed using the described method. The validity of the agreement is related to e-commerce transactions if it meets Article 1320 of the Civil Code, including the agreement of those who bound themselves, the ability to make an agreement, the existence of a certain matter, and the existence of a halal cause. Law enforcement efforts in resolving e-commerce transaction disputes are carried out preventively through legislation and repressive measures through litigation and non-litigation channels such as through arbitration, consultation, mediation, conciliation, or expert judgment. In addition, it can also be resolved through BPSK, LPKSM, and the Directorate of Consumer Protection.